Designing efficient paths between base station and multi mobile sink nodes to transfer data in wireless sensor networks based on anchor nodes - Z. Abdullah, Mahmood; A. Shiltagh, Nadia; R. Zarzor, Ahmed (International Journal of Engineering and Technology, 2018)
A Wireless Sensor Networks (WSNs) has been implemented in a lot of applications such as smart homes, military, healthcare, etc. Thus, integrated all WSNs in a single large geographical network, which poses major challenge for designing efficient paths to transfer data be-tween all these WSNs. This study proposes a technique to design best short paths between multi-mobile sink nodes (SN) and single Base Station (BS) based on Anchor nodes (AN). The ANs are used to specify the BS location, with one Reference node that used to specify a mobile SN location in each WSN. Although, the best path is selected based on a number of hops, the distance between each SN and the B S. Furthermore, the path quality is measured by using Quality of Service (QoS) parameters. In this study, two scenarios are implemented using NS software (version 2.30) on the network framework consisted of four WSNs, with four static or mobile SNs, connected to six ANs around a single BS and four reference nodes. The simulation results show that the dynamic paths with mobile SNs improved overall net-work performance, because they give higher throughput and minimum delay and dropped packets in comparison to static paths with static SNs.Â Â